Zimowe ekstrema termiczne w Polsce i ich cyrkulacyjne uwarunkowania - Tomczyk, Arkadiusz M.; Miś, Filip (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
The study’s objective was to determine the spatial and temporal variability of occurrence of extremely warm days in winter in Poland in 1966/67–2020/21, and to determine the effect of atmospheric circulation on their occurrence. An extremely warm day is defined as a day with a maximum daily air temperature equal to or higher than the value of the 95. percentile. The effect of atmospheric circulation on the occurrence of the analyzed days was determined on the basis on two teleconnection patterns, namely the North Atlantic Oscillation (NAO) and Scandinavia (SCAND). The progressing warming translated into increasingly frequent occurrence of extremely warm days. In terms of the abundance of such days, the following winters stood out in the entire multiannual period: 1989/90, 2015/16, 2006/07, and 2001/02.